Análise de retorno de investimento e viabilidade econômica em projetos de eficiência energética aplicados à Reitoria do Instituto Federal do Triângulo Mineiro - TAGLIAFERRO, Mateus Emanuel (2019)
The development of this study allows the public manager to understand the factors that must be observed in the implantation of a photovoltaic power, as well as to verify its results, allowing a critical analysis for future contracts. A grid-connected photovoltaic power system, when compared to other alternative sources of energy, have low complexity of installation and operation. In addition, because it is installed near the place of electric power consumption, they allow to postpone investments in electric power transmission systems. In addition, they might reduce technical losses in the grid. The pilot project for the implementation of a photovoltaic electric power generation system at the Rectory of the Federal Institute of Education, Science and Technology of the Triângulo Mineiro (IFTM) will allow the verification of electric energy savings over the months and will allow the analysis of the return on investment, comparing the cost of capital invested. To be attractive, the investment proposal should at least return the value referring to current and low risk applications.